Effects of calcination temperature on the catalyst performance in a CO2 hydrogenation reaction - et.al, Nur Insyirah Zulkifli (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cu/ZnO catalysts were synthesized on Al2O3-ZrO2 support via impregnation method with addition of manganese and niobium promoters. Samples were calcined at 181, 350 and 518 ºC. Different characterization techniques such as H2-TPR and CO2-TPD were used to study the catalytic reduction behavior and catalytic basicity, respectively. H2-TPR studies shows that all the catalysts reduction occurred on the range of temperature between 237 ºC and 265 ºC. The CO2-TPD profiles showed that the calcination temperature significantly influences the basicity of the catalyst and the catalyst calcined at 35 0oC was proved to contain the highest amount of the basic sites. Furthermore, the characterization results were validated through analyzing of the catalyst performance during CO2 hydrogenation reaction and the results indicate that highest methanol yield of 12.2 % were obtained from the catalyst that calcined 350 oC.